Abrupt increased serum creatinine in a hyperferritinemia patient treated with deferoxamine after cord blood transplantation: a case report with literature review - Hirokazu Nakayama; Yoshimasa Kamoda; Michiya Tanuma; Toshiaki Kato; Kensuke Usuki (BMC, 2023)
Abstract Background Erythrocyte transfusion is an indispensable component of supportive care after hematopoietic stem cell transplantation (HSCT). However, HSCT recipients are susceptible to the development of acute kidney injury (AKI) with multifactorial causes. We report a case of a rapid elevation in serum creatinine associated with deferoxamine after cord blood transplantation (CBT). Case presentation A 36-year-old Japanese male diagnosed with relapsed Philadelphia-positive acute lymphoblastic leukemia received CBT. At day 88 post-CBT, multidrug-resistant Pseudomonas aeruginosa (MDRP) was isolated from urine culture. Subsequently, colistin 200 mg/day was administered parenterally for treatment of epididymitis from day 91 to 117 post-CBT. Despite concomitant administration of potential nephrotoxic agents such as piperacillin-tazobactam, acyclovir, and liposomal amphotericin B, no development of AKI was observed during this period. At day 127 post-CBT, MDRP was detected in blood and urine cultures, and colistin 200 mg/day was re-started parenterally. Due to extremely higher ferritin level, deferoxamine was administered intravenously at day 133 post-CBT. While serum creatinine was 1.03 mg/dL before starting deferoxamine, the level increased to 1.36 mg/dL one day after commencing deferoxamine (day 134 post-CBT), and further increased to 2.11 mg/dL at day 141. Even though colistin was discontinued at day 141 post-CBT, serum creatinine continued to increase. Deferoxamine was withdrawn at day 145 post-CBT, when serum creatinine peaked at 2.70 mg/dL. In addition, no cylinduria is observed during the period of development of AKI. In adverse drug reaction (ADR) assessment using Naranjo probability score, the scores of 3 in deferoxamine and 2 in colistin, respectively, indicated "possible" ADR. However, while colistin-associated AKI manifested early onset, recovery time within 2 weeks after discontinuation and development of cylinduria, this case was discordant with the properties. Furthermore, in the literature review, development of AKI within 1 day, including sudden increase in serum creatinine or abrupt reduction in urine volume, was reported in 3 identified cases. Conclusions We considered the rapid creatinine elevation to be the result of deferoxamine rather than ADR caused by colistin. Therefore, careful monitoring of kidney function is required in recipients of HSCT treated with deferoxamine.